The Application of Canva as Interactive Media in 21st Century Learning - Musannadah, Siti; Jannah, Siti Nur (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The purpose of this activity is to describe the Canva application as an interactive medium for learning. The research method used is the literature review research method, namely comparing data from several journals, which have been analyzed and summarized based on the author's experience, existing theories, and models. The results show that Canva, as a graphic design application, plays a crucial role in learning by facilitating teacher creativity and developing communicative learning media. With a simple interface and complete editing features, Canva makes it easy for teachers to create various learning materials, from posters to videos. However, Canva has some drawbacks, such as paid features and limitations of the free version. The solution is Canva Pro Education with email Belajar.id, providing free access to premium features. With various templates, Canva is an effective tool for improving the quality of learning and supporting teacher creativity. Examples of interactive learning media, such as student worksheets, learning videos, PowerPoint presentations, and educational game cards, can be easily created via Canva. In this way, Canva positively contributes to creating exciting and varied learning.